STUDI POTENSI SUMBER DAYA AIR UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DI PEKON TUGU RATU KECAMATAN SUOH KABUPATEN LAMPUNG BARAT PROPINSI LAMPUNG - Dyah Indriana Kusumaastuti; Dwi Joko Winarno; Humaidi Humaidi (UNIVERSITAS LAMPUNG, 2015)
Water resources in Western Lampung Regency particularly the sub-District Suoh has a lot of po- tential hydropower, which have not been able to optimally utilized as electrical energy. So that one of the optimal effort that can be done is by using microhydro energy. Location of the research is in the Way Sekanda river tributary of the Way Semaka river. Process analysis using primary data in the form of a cross section of the river cross-section of data and flow velocity of Way Sekanda, than secondary data from hourly discharge data from the watershed outlet Way Besai for 11 (eleven) years, the real-time of rainfall in Tugu Ratu village from Septem- ber 2012 to September 2014 and watershed area derived from Geographic Information System. Analysis starts from the formation of spatial data maps of Way Semaka watershed, Way Besai wa- tershed and Way Sekanda watershed using ArcGIS program. Research method includes regional- ization Way Semaka watershed and Way Besai watershed, estimation the dependable discharge (Q 80% ) using FDC method, measured discharge calculation of Way Sekanda river, correlation be- tween discharge FDC method and measured discharge and calculate the electric power which can be generated. The formation of the watersheds were done using spatial data analysis and were found that the area of Way Semaka watershed is 731,0783 km 2 , Way Besai watershed is 415,0393 km 2 , Way Sekanda watershed is 1,48 km 2 . Using measured discharge recorded in Way Besai watershed and the application of regionalization method, the discharge at Way Semaka and Way Sekanda can be estimated.This is evidenced by the amount of discharge calculated by the method of Flow Dur- ration Curve is not much different from the magnitude of the discharge measured in the field. Q80 % with FDC method (Flow Duration Curve) to Way Sekanda River is 0,0312 (m 3 /sec), while the measured discharge in location of Way Sekanda micro hydro power plants (MHP) 0,0314 (m 3 /sec). From the calculation of the electric power in Way Sekanda by using dependable of dis- charge 50% (Q 50% ) of 0,0592 m 3 /s it is obtained the electricity power with an efficiency of 60 % is 2,7479 kW, while the electric power with an efficiency of 90 % is 4,1219 kW. Therefore Way Sekanda River is potential for micro hydro power plants (MHP).